Imatinib dose reduction in major molecular response of chronic myeloid leukemia: results from the German Chronic Myeloid Leukemia-Study IV - Michel, Christian; Saußele, Susanne; Fabarius, Alice; Ho, Anthony Dick; Hehlmann, Rüdiger (Haematologica, 2019)
Standard first-line therapy of chronic myeloid leukemia is treatment with imatinib. In the randomized German Chronic Myeloid Leukemia-Study IV, more potent BCR-ABL inhibition with 800 mg (‘high-dose’) imatinib accelerated achievement of a deep molecular remission. However, whether and when a de-escalation of the dose intensity under high-dose imatinib can be safely performed without increasing the risk of losing deep molecular response is unknown. To gain insights into this clinically relevant question, we analyzed the outcome of imatinib dose reductions from 800 mg to 400 mg daily in the Chronic Myeloid Leukemia-Study IV. Of the 422 patients that were randomized to the 800 mg arm, 68 reduced imatinib to 400 mg after they had achieved at least a stable major molecular response. Of these 68 patients, 61 (90%) maintained major molecular remission on imatinib at 400 mg. Five of the seven patients who lost major molecular remission on the imatinib standard dose regained major molecular remission while still on 400 mg imatinib. Only two of 68 patients had to switch to more potent kinase inhibition to regain major molecular remission. Importantly, the lengths of the intervals between imatinib high-dose treatment before and after achieving major molecular remission were associated with the probabilities of maintaining major molecular remission with the standard dose of imatinib. Taken together, the data support the view that a deep molecular remission achieved with high-dose imatinib can be safely maintained with standard dose in most patients. Study protocol registered at clinicaltrials.gov 00055874.